Enhancing the Creative Economy of MSMEs in Villages via Business Digitalization: KKN involvement Campaign in Serdang Wetan Village - Nasution, Atiqi Chollisni; Rosita; Wulandari, Fithri; Alfiah; Amanda; Kholifah, Nur; Rahayu, Pipih; Fauziah, Delia Isna; Sabrina, Meriana Khalifah (Indonesian Journal of Community Services Cel, 2026)
Background: The Community Service Program (PKM) will be implemented through Student Community Service Program Course (KKN) in July-August 2025 in Serdang Wetan local, Legok District, Tangerang Regency, with the objective of enhancing the competitiveness of local MSMEs by strengthening the creative economy through the digitization of business. MSME partners predominantly face challenges like insufficient company legitimacy, limited product branding expertise, inadequate digital and financial literacy, and a lack of knowledge in electronic payment technology and digital promotional methods.Aims: Enhancing the creative economy of MSMEs in Serdang Wetan village via business digitalization.Methods: The PKM implementation method utilizes a "participatory and direct assistance" approach, which includes: (1) facilitation of Business Identification Number (NIB) acquisition; (2) activation of the QRIS payment system; (3) registration of business locations on Google Maps; (4) training in digital branding and promotional media design; and (5) basic financial literacy counseling, specifically concerning the calculation of Cost of Goods Sold (COGS) and essential cash flow management.Result: The examination's outcomes suggested that between the 25 MSME participants, 80% accomplished NIB, 72% enabled QRIS, and 76% registered on Google Maps. Furthermore, there has been a significant improvement in branding awareness and financial literacy, demonstrated by an average increase of 35% in pre-test and post-test scores, coupled with an enhancement in corporate digital visibility, as reflected by the growth in online customer engagement. The results demonstrate that the goals of PKM activities have been achieved, particularly in improving the readiness of village MSMEs to adopt digitalization and participate in the creative economy ecosystem. This program promotes the development of a sustainable and reproducible digital empowerment approach for MSMEs in communities with similar features.